Philosophical and Historical Foundations of the Establishment of Blasphemy Articles in the Criminal Code (KUHP) - Lalu Arasistawa (Perantara Law Review, 2024)
Research Article 156a in the Criminal Code (KUHP) is a legal basis related to blasphemy in Indonesia, which aims to maintain harmony of diversity. This study aims to examine the philosophy of the formation of the article, by tracing the juridical, historical and sociological foundations behind its existence. The research method used is a normative juridical approach by analyzing legal documents, Supreme Court jurisprudence, and Decree No. 1/PNPS/1965 on the Prevention of Abuse and/or Blasphemy of Religion. The results show that Article 156a has roots in the British Indian Penal Code and was adopted through the influence of jurisprudence, then affirmed in the era of President Soekarno to respond to social dynamics and demands of conservative Islamic organizations against belief teachings that are considered deviant. The article reflects the need to protect state-recognized religions from potential blasphemy, although its use is often debated in relation to freedom of religion and expression. In conclusion, the establishment of Article 156a was a legislative effort to balance human rights with social stability in the context of religious plurality in Indonesia, from which emerged the blasphemy law and the beginning of Article 156a's inclusion in the composition of the Criminal Code (KUHP).